Detection of seismograph signal using fiber bundle sensor - Yasin, M.; Apsari, Retna; Ningsih, Kristia; Yhuwana, Y.G.Y.; Zulkarnaen, M.; Djamal, Mitra; Meilano, Irwan; Evita, Maria; Aminah, Nina Siti; Srigutomo, Wahyu; Setiawan, Ari; Darmawan, Herlan; et al. (Elsevier, 2020)
The improvement of an external fiber optic sensor both in design and in operational was conducted based on displacement measurement. The purpose of the investigation is to measure the frequency and the amplitude of seismograph signal using the fiber-optic displacement sensor. This sensor setup consists of an optical fiber transmitter, an optical fiber bundle probe, photodiode detector and a seismograph stimulator. The use of stimulator is as a volcano signal model for the testing process. The sensor has the capability to measure the seismograph signal from 0.5 to 1.5 Hz and the linearity is more than 99 %. The proposed sensor is simple, sensitive, provides high dynamic range, and offers lower cost of the fabrication and thus it is suitable to be applied in real field. Furthermore, this sensor generates more excellent result in accuracy and reliability. © 2020 Elsevier GmbH